Implementation of Character Education Through P5P2RA Based on Local Wisdom - Andini, Tiara; Usman, Asep Tutun; Nazib, Fiqra Muhamad; Masripah, Masripah (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
Character education plays a central role in shaping students into individuals with integrity and competitiveness. One of the approaches used to instill character values is through the Projek Penguatan Profil Pelajar Pancasila dan Rahmatan Lil’Alamin (P5P2RA) based on local wisdom. This study aims to examine the planning, implementation, and evaluation processes, as well as to identify the supporting and inhibiting factors in the implementation of character education through P5P2RA grounded in local culture. A descriptive qualitative method was employed, with data collected through in-depth interviews, field observations, and documentation. The study focuses on the application of character values such as faith and piety, love for the homeland, mutual cooperation, responsibility, creativity, proper manners (ta’abbud), and a dynamic and innovative attitude (tatawur wa ibtikar) within project-based learning activities that highlight local potential. The findings reveal that the implementation of P5P2RA based on local wisdom is fairly effective in developing students' character. Activities such as constructing miniature traditional houses and showcasing student work (Gelar Karya) encouraged students to collaborate, think critically, and appreciate local culture. However, the program still faces several challenges, including low active student participation in project creation, lack of enthusiasm, and limited transportation funding for field exploration activities. Nevertheless, the school has demonstrated its commitment to overcoming these obstacles by optimizing internal resources and implementing innovative strategies.